MANAGEMENT OF LOCAL WISDOM DEVELOPMENT TO IMPROVE STUDENT CHARACTER AT LEADING SCHOOLS IN MERTOYUDAN DISTRICT - Maharani, Zahra Yasmin Dinda; Imron, Imron (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
This research explores how management develops local wisdom to enhance student character in schools in Mertoyudan District. It finds that local wisdom practices at MI Ma'arif Bulurejo and Al Firdaus Islamic Elementary School significantly improve students' character and spirituality. Using a qualitative descriptive approach, data were collected through interviews, observations, and documentation, with triangulation for data validity. Findings reveal that school leaders and teachers actively preserve both tangible (e.g., Suronan, Nyadran) and intangible local wisdom (e.g., verbal advice, traditional practices) at these schools. Furthermore, school principals, teachers, and parents play a crucial role in shaping student character through regular local practices and fostering positive habits beyond the school environment. These activities have a notable impact on students, helping them develop spirituality, discipline, curiosity, teamwork, and good social relations, ultimately improving their overall character.